Sea Lice ( Lepeophtheirus salmonis ) Harbour Putative Fish Pathogens: Insights From Illumina and Nanopore Sequencing - B. Klimesova; N. M. Ruane; R. Domingo‐Bretón; F. Moroni; F. Naya‐Català; J. Pérez‐Sánchez; K. O'Dwyer; O. Lyashevska; H. Rodger; A. Talbot (Journal of Fish Diseases, 2026)
Ectoparasites that penetrate host skin can act as biological or mechanical vectors for pathogens and, in some cases, serve as reservoirs. Crustacean ectoparasites of fish are potential vectors of pathogens, which is especially relevant for obligate pathogens (e.g., Aeromonas salmonicida ) with limited seawater survival. Sea lice ( Lepeophtheirus salmonis ), affecting Atlantic salmon, cause dermal damage and can facilitate secondary infections, resulting in economic losses. While the physical impact of sea lice is well known, their role in pathogen transmission is less clear. The gut bacterial microbiome of lice collected over four months from a salmon farm in Ireland was analysed using Illumina MiSeq and Oxford Nanopore Technologies (ONT) PromethION sequencing for comparison. Illumina and Nanopore sequencing identified 15 and 24 genera of known fish pathogens, respectively. Moreover, Nanopore data revealed up to 15 putative pathogenic species, including Tenacibaculum maritimum , T. dicentrarchi and Vibrio anguillarum , causative agents of tenacibaculosis and vibriosis. The results of this study provide a gut bacterial microbiome characterisation of L. salmonis in a commercial aquaculture setting and demonstrate the potential of sea lice to act as pathogen vectors or reservoirs. These findings have important implications for pathogen surveillance, management, and prevention strategies in salmon aquaculture.